Effect of SSC Loading on the Microstructural Stability SSC-SDCC Composite Cathode as New Potential SOFC - Mohammad, Siti Fairus; Ahmad, Sufizar; Abdul Rahman, Hamimah; Muchtar, Andanastuti (International Journal of Integrated Engineering, 2019)
The composite cathode, samarium strontium cobaltite-samarium doped ceria carbonate (SSC-SDCC), was developed and scrutinised as for potential cathode materials in solid oxide fuel cell (SOFC) applications. The microstructural and physical characteristics of composite cathode powders have been explored in terms of SSC loading and calcination temperature. SSC-SDCC composite powders were intimately mixed by employing fast high energy ball milling (HEBM) method with different SSC loadings (50-70 wt.%) and subjected to various calcination temperatures from 600 °C to 750 °C. Subsequently, the calcined cathode powders were then used to fabricate composite pellets using a uniaxial press and undergo sintering process at a temperature of 600 °C. Microstructural behaviour of the composite cathode powders was examined using X- Ray diffraction (XRD) and Energy Dispersive Spectroscopy (EDS). The physical stability sintered composite pellets were also investigated from the observation on Scanning Electron Microscopy (SEM). All samples retained their microstructural compatibility and stability, with the incorporation of carbonate after various processes. The composite cathode of SSC-SDCC55 with calcination temperature at 750 ºC was chosen to be used as a potential cathode material for LTSFOC performance regarding the optimum chemical and microstructural properties.